Nilai Etika dan Moral dalam Pendidikan Jasmani Ditinjau dari Perspektif Filsafat Pendidikan: Kajian Literatur - Shany Kurniawan; Erlangga Syahir; Zainal Arif Harahap; Bina Ojahan Simanjuntak; Josrel Junawi Eklesia Hutasoit; Alexsander S; Nurkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine ethical and moral values in physical education from the perspective of educational philosophy through a literature review approach. Physical education serves not only as a medium for developing physical fitness and motor skills but also as an important instrument for character building among students. This study utilizes various scientific literature sources related to physical education, educational philosophy, ethics, morality, and character education. The findings indicate that physical education contains numerous ethical and moral values, including sportsmanship, honesty, discipline, responsibility, cooperation, and respect for others. From the perspective of educational philosophy, physical education is viewed as an integral part of the educational process aimed at developing individuals holistically, encompassing physical, intellectual, social, emotional, and moral dimensions. Through physical activities and sports, students gain meaningful experiences that support the internalization of moral values and the development of positive character traits. Therefore, physical education should be implemented in a balanced manner that integrates physical development with the cultivation of ethical and moral values to foster healthy, responsible, and well-characterized individuals in society.